Synthesis and antibacterial activity of some novel isoxazolyl schiff’s bases - RAMU KAKKERLA; NAMRATHA VADDIRAJU; RAMCHANDER MERUGU (International Journal of Pharma and Bio Sciences, 2016)
A series of isoxazolyl schiff’s bases (3a-h) were synthesized from N-(5-methyl-3-isoxazolyl)-3-oxobutanamide (1) .The compound (1) upon heating with different primary amines in methanol furnished (E)-3-(methylimino)-N-(5-methylisoxazol-3-yl)butanamides (3a-h) in excellent yield. The structure of all the synthesized compounds has been established by IR, 1H NMR, 13C NMR and mass spectral data. All the synthesized compounds (3a-h) were screened for antibacterial activity against two Gram-positive (Bacillus subtilis MTCC 121 and Staphylococcus aureus MTCC 96) and two Gram-negative (Escherichia coli MTCC 43 and Klebsiella pneumoniae MTCC 530) bacterial strains. The Schiff’s bases (E)-N-(5-methylisoxazol-3-yl)-3-(phenylimino)butanamide 3c ( MIC values 11±0.28, 14±0.10, 12±0.31,14±0.31, at 40µg/µL,) and (E)-3-(benzylimino)-N-(5-methylisoxazol-3-yl)butanamide 3f ( MIC values 12±0.38, 14±0.10, 13±0.21,14±0.32, at 40µg/µL,) showed significant activity against all the bacteria tested compared to other compounds in this series. All other compounds except compounds 3a and 3b have shown considerable antibacterial activity against different bacterial stains. Compound 3a and 3b could show activity only at the high concentration. Furthermore, substitutions at phenyl nucleus have not much affected the antibacterial activity.